Development of Religious Moderation Teaching Materials in Character Education Courses at Public Christian Religion Institute (IAKN) Ambon - Herly Janet Lesilolo (Journal of Social Science, 2022)
The development of religious moderation teaching materials in character education courses at the Ambon State Christian Institute is one form of implementing religious moderation in the Ambon IAKN environment. In addition, this research also aims to deepen and broaden the knowledge of IAKN Ambon students about religious moderation. The type of research is Research and development, using the development model of M. Alessi and Stanley R. Trollip (2001) with four stages, namely, planning, design, development and Disseminate. The results of the study indicate the feasibility of teaching materials for the five main materials assessed by the validator, namely: the mean score of 3.25 which is qualitatively included in the very feasible category. Material validation on the content aspect with an average score of 3.08 with a very decent category. The results of the test with students for the small group obtained 3.16 and for the large group test it was obtained 3.09. The hope in the future is that the development and internalization of religious moderation will not only end in religious moderation teaching materials. However, it is necessary to carry out a follow-up plan with parties who are directly related to the learning process and student development. In relation to this follow-up plan, it can be proposed to, 1) review the IQF so that the values ​​and application of religious moderation are given weight, and 2) research studies and community service can focus on the concept of religious moderation. However, it is necessary to carry out a follow-up plan with parties who are directly related to the learning process and student development. In relation to this follow-up plan, it can be proposed to, 1) review the IQF so that the values ​​and application of religious moderation are given weight, and 2) research studies and community service can focus on the concept of religious moderation.